Assessment of Time-Varying Waveform Distortion Measured in a Railway Traction Converter Station - Rafael S. Salles; Tommy Hjertberg; Mats Wahlberg; Sarah K. Ronnberg (IEEE Access, 2025)
The waveform distortion interactions and time-varying behavior in electric railway power systems (ERPS) are explored in this paper by investigating measurements from a traction converter station. The paper proposes a methodology aimed at contributing to three aspects: screening detailed measurements with high resolution in time and frequency, comprehensively assessing waveform distortion parameters of the system, and developing a time-varying framework to assess waveform distortion interactions and sub-1-min variations in the railway grid. Specific focus is given to identifying disturbance sources and patterns during operation, including limitations of traditional methodologies based on aggregated values and addressing the challenges posed by the differences between the two electromagnetic environments (railway grid and public grid). The results propose new indices ( $z\text {-}WDSV{,z\text {-}WDSV}_{w}$ ) for evaluating waveform distortion in ERPS, highlighting the suitability of the methodology for assessing time-varying interactions and probabilistic aspects. The proposed framework can determine and quantify the frequency-domain components impacted by the operation of vehicles in the traction sections. Additionally, the limitation of longer measurement intervals is confirmed by the relationship between the aggregated value and variance due to the rapid variation caused by rolling stock operations. Other aspects of mechanisms involving waveform distortion on both sides of the traction converter station are discussed.